Study on the relationship between viral inactivation and alkyl chain length of benzalkonium chloride - Ikumi Takada; Atsushi Miyazaki; Chisato Igarashi; Yukiko Yamawaki; Atsuko Hayase; Takuya Mori; Takaya Sakai (PLoS ONE, 2025)
Alkyldimethylbenzylammonium chloride (BAC), a quaternary ammonium salt surfactant, is commonly utilized as a sanitizer and disinfectant. Concerns have emerged regarding the increasing global exposure to BAC, emphasizing the need for strategies to maximize its efficacy while minimizing its usage. Therefore, it is crucial to understand BAC’s effects on bacteria and viruses, and its mechanism of action. Our previous research demonstrated that BAC micelles solubilizes the lipid bilayer of viruses, significantly enhancing virus inactivation efficacy at concentrations exceeding the critical micelle concentration (CMC). We focused on the alkyl chain length of BAC to elucidate how variations in CMC, driven by differences in alkyl chain length, influence virus inactivation activity. We measured CMC and assessed influenza virus inactivation for benzyldodecyldimethylammonium chloride (C12BAC), benzyltetradecyldimethylammonium chloride (C14BAC), benzylhexadecyldimethylammonium chloride (C16BAC), and their mixtures. The results showed that both BACs with a single alkyl chain length and mixed BACs exhibited significantly enhanced inactivation activity at concentrations of the CMC or above. Notably, BAC mixtures with comparable CMC values showed similar virucidal activity, suggesting that CMC can serve as a useful indicator in designing BAC mixtures aimed at virus inactivation, leading to the development of compositions with enhanced virus inactivation at lower doses. However, when the bactericidal activity of each BAC mixture against E. coli was tested under the same conditions, a significant bactericidal effect, of at least 3 Log10, was observed even at concentrations below CMC. This suggests that the bactericidal activity of BAC is not due to the micellization at CMC, but rather to the contribution of BAC monomers, indicating a distinct difference in the mechanism of action of BAC against viruses and bacteria. Therefore, when formulating BAC-based disinfectants, it is essential to assess the inactivation efficacy against both bacteria and viruses to ensure sufficient virus inactivation.